2019
DOI: 10.1038/s41598-019-38656-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ologen matrix implant in Ahmed Glaucoma Valve Implantation

Abstract: To determine the efficacy and safety of the Ologen collagen matrix adjunctive to Ahmed valve surgery. A randomized prospective multicentre clinical trial involving 58 patients that were followed for one year. Conventional surgery with Ahmed valve was performed in 31 eyes (Control group/CG) and in 27 Ologen (Ologen group/OG) was placed over the valve’s plate. Baseline data: age, corneal thickness, intraocular pressure(IOP) and antiglaucoma medications.Postoperative data (days 1, 7 and months 1, 3, 6 and 12): IO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 25 publications
(34 reference statements)
0
17
0
Order By: Relevance
“…12 Months 0 (6 Eyes) p = 0.0008 2.1 ± 1.4 (9 Eyes) p = 0.7 p = 0.002 Final 0.2 ± 0.4 (6 Eyes) p = 0.001 2.0 ± 1.0 (5 Eyes) p = 0.6 p = 0.003 of GDD implantation has predominantly fallen out of favor as studies have either shown an increase in bleb leaks and complications secondary to hypotony or no significant difference in IOP or number of glaucoma medications [22]. More recently, studies have utilized Ologen in conjunction with AGV implantation in adult glaucomas [13,14,23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Months 0 (6 Eyes) p = 0.0008 2.1 ± 1.4 (9 Eyes) p = 0.7 p = 0.002 Final 0.2 ± 0.4 (6 Eyes) p = 0.001 2.0 ± 1.0 (5 Eyes) p = 0.6 p = 0.003 of GDD implantation has predominantly fallen out of favor as studies have either shown an increase in bleb leaks and complications secondary to hypotony or no significant difference in IOP or number of glaucoma medications [22]. More recently, studies have utilized Ologen in conjunction with AGV implantation in adult glaucomas [13,14,23].…”
Section: Discussionmentioning
confidence: 99%
“…To date, three studies have reported the use of Ologen as an adjuvant for AGVs in adults [13,14,23]. The first showed that increased AGV success correlated with the thickness of the Ologen disc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biodegradable collagen matrix is placed over the drainage device implant, and influences healing by causing fibroblasts and myofibroblasts to ingress into the pores and secrete connective tissue, thus forming a loose matrix 9 . Although the safety and efficacy of ologen during AGV implantation for human ophthalmological conditions remains controversial, we hypothesized that ologen may decrease the complications associated with MMC and 5‐FU among dogs 10,11 . We think that this surgical method can increase the surgical success rate and reduce the number of anti‐glaucoma medications required after operation 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the safety and efficacy of ologen during AGV implantation for human ophthalmological conditions remains controversial, we hypothesized that ologen may decrease the complications associated with MMC and 5‐FU among dogs 10,11 . We think that this surgical method can increase the surgical success rate and reduce the number of anti‐glaucoma medications required after operation 10,11 . Although numerous studies have investigated the clinical efficacy of ologen for AGV surgery in humans, to our knowledge, no studies have reported cases of AGV implantation surgery using ologen for treating canine glaucoma.…”
Section: Introductionmentioning
confidence: 99%